Singapore’s National Union Catalogue and Virtual Union Catalogue : what’s best and next? - Soh, Lin Li (2010)
There are two Union Catalogues in Singapore, both serving as the integrated national platform for information retrieval of all materials in Singapore libraries. Undoubtedly, there are overlapping and duplication of functions and services between these two catalogues. The objective of this dissertation is to study the Singapore national Union Catalogue (NUC) and Virtual Union Catalogue (VUC). so that a well-researched recommendation could be made on the future development of Union Catalogues in Singapore. The research methodology adopted for this dissertation is to carry out an in-depth literature review relating to overseas and local Union Catalogues to better understand the existing models and possibly future trends in this area. To find out more about the case studies, interviews with overseas and local experts were conducted. These interviews strengthen the findings as they are first-hand information shared by the professionals. A detailed comparison study of the functions, features and interfaces between the two catalogues was done, together with Strength, Weakness, Opportunities and Threat (SWOT) analyses of the catalogues. These findings were discussed at length, together with possible future scenarios of these catalogues. At the end of the findings, the most probable scenario was derived with a recommendation for the future roadmap of Union Catalogue in Sinagapore.